USE OF INFORMATION TECHNOLOGIES FOR THE PREVENTION OF PROFESSIONAL BURNOUT OF TEACHERS - A. E. Makarenko (Вестник университета)
Professional burnout of the high school tutors and its negative impact on the educational process and the state of health of teachers, have been revealed in the article, signs, indicating the systemic nature of the problem, have been described. Strategies of overcoming such professional burnout have been considered, the preference of the problem-oriented strategy has been noted. The results of the analysis of the time spent by the teacher in the formation of assignments have been presented. The expediency of using information technologies as a tool to reduce the load on the teacher by reducing the time required to prepare for practical and laboratory classes has been substantiated. The stages of preparation for classes, that should be automated, have been highlighted.